Finite Volume Solution of Non-Newtonian Casson Fluid Flow in A Square Cavity - Mehmood, S.; Nawaz, M.; Ali, A. (Communications in Mathematics and Applications, 2018)
A two dimensional unsteady flow of non-Newtonian fluid in a square cavity is investigated numerically by using finite volume method based on staggered grids. The discretized equations are integrated by using second order Adams-Bashforth time advancement scheme togather with pressure correction approach. Error history for velocities and pressure are recorded for high Reynolds number when grid resolution is \(128×128\). The results are also compared with already published work for special case. An excellent agreement is observed. The behavior of velocity components are studied for different values of non-Newtonian parameter $β$, the Casson fluid parameter.